The Role of the State in Economic Activity: Determinants and Obstacles Facing the (Gulf Cooperation Council Countries): the international and political journal - م.د لواحظ خليل ابراهيم (The International and Political Journal, 2025)
The research addressed the role of the state in the economic activity of the Gulf Cooperation Council countries and the economic methods and programs used to manage this activity. It shed light on the basic concepts of economic growth strategies, the most important economic stages and achievements of these countries, and the impact of state activity on the economic sector. It clarified an important problem represented by the state's influence on the determinants and huge transformations in economic activity and progress, and the role of these determinants in facing obstacles. The descriptive approach was used to study the research phenomenon. The research reached a number of results, the most important of which is that this council achieves benefits and economies of scale and reduces transaction costs in the various markets it deals with. The research also concluded that the Gulf Cooperation Council at its current level has not reached the stage of economic integration achieved by a number of regional and global economic blocs.